Mapping cohesive device usage to analyse non-native writers’ needs in academic English - Ashadi, Ashadi; Margana, Margana; Mukminatun, Siti (LingTera, 2020)
Native or non-native English-speaking academics are compelled to write scientific articles in internationally reputable indexed journals today. With high demand of academic English, more and more articles are rejected by the editorial board for various reasons, mainly in the cohesion and coherence of their writing. This research seeks to map the types and patterns of cohesive device used to support the coherence of scientific articles. Employing a descriptive qualitative approach, this study compared the use of cohesion devices (CD) by both groups’ writing (native & non-native) to further bridge the difficulties faced by non-native writers in shaping their academic writing cohesively and coherently. This study may also serve as a needs analysis that allows for the creation of models, materials, and teaching approaches to scientific article writing for learners of English as a foreign language.